Intelligent Technologies for Interactive Entertainment 5th International ICST Conference, INTETAIN 2013, Mons, Belgium, July 3-5, 2013, Revised Selected Papers - Mancas, Matei; d$1 (BAlessandro, Nicolas.s; Siebert, Xavier; Gosselin, Bernard; Valderrama, Carlos; Dutoit, Thierry; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the proceedings of the 5th International Conference on Intelligent Technologies for Interactive Entertainment, INTETAIN 2013. The 23 full papers presented were carefully selected from numerous submissions. The conference aims at enhancing the understanding of recent and anticipated advances in interactive technologies, and their applications to entertainment, education, culture, and the arts. The papers are grouped in topical sections on linked media, gaming technologies, and technologies for live entertainment.
Personalized Summarization of Broadcasted Soccer Videos with Adaptive Fast-Forwarding -- Real-Time GPU-Based Motion Detection and Tracking Using Full HD -- Feeling Something without Knowing Why: Measuring Emotions toward Archetypal Content -- Web and TV Seamlessly Interlinked: Linked TV -- Interactive TV Potpourris: An Overview of Designing Multi-screen TV -- 3D Head Pose Estimation for TV Setups -- Visualizing Rembrandt: An Artist$1 (Bs Data Visualization -- Stylistic Walk Synthesis Based on Fourier Decomposition -- Automatically Mapping Human Skeletons onto Virtual Character -- Medianeum: Gesture-Based Ergonomic Interaction -- DanSync: A Platform to Study Entrainment and Joint-Action during Spontaneous Dance in the Context of a Social Music Game -- Accuracy Study of a Real-Time Hybrid Sound Source Localization -- Image Surround: Automatic Projector Calibration for Indoor Adaptive Projection -- Multimodal Analysis of Laughter for an Interactive System.s
Keywords: Computer science; Computer vision; Computer Science; Media Design; User Interfaces and Human Computer Interaction; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Applications